Upaya Penegakan Hukum Terhadap Anak Pelaku Tindak Pidana Penyalahgunaan Narkotika - Hidayat, Sa'ban Alfin; Wahyudi, Setya; Budiyono (Acten Journal Law Review, 2025)
Children as a vulnerable group are increasingly involved as perpetrators or victims in the distribution and abuse of narcotics. This situation demands a legal response that is not only repressive, but also solution-oriented and just. This article aims to analyze law enforcement against children who are perpetrators of narcotics abuse, with a normative legal approach. The main focus of this study is to assess the suitability between the law enforcement process against children and the objectives of punishment as regulated in the national legal system. This study examines a number of regulations, including Law Number 35 of 2009 concerning Narcotics, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, and Law Number 35 of 2014 concerning Child Protection. The method used in this study is conducted with normative legal research. The approach method used in compiling this writing is normative legal research and also uses a deductive thinking method. The results of the study show that, although the regulation has placed rehabilitation and restorative justice as the main approach, implementation in the field still faces obstacles such as limited facilities, human resources, and minimal coordination between institutions. Factors that influence children to become perpetrators of drug abuse are legal substance, legal structure, facilities, legal culture and society. The most influential factor is the child's own internal. Law enforcement against perpetrators of drug abuse crimes committed by children has been effective. The role of parents to educate children properly so that they are not easily influenced to do things that violate the law.